Attitudes of Nurses Towards Searching Online for Medical Information for Personal Health Needs: Cross-Sectional Questionnaire Study - Zigdon, Avi; Zigdon, Tamar; Moran, Daniel Sender (JMIR Publications, 2020)
BackgroundUse of online clinical health care information has become part of the skill set required by medical teams. Nurses believe that information quality and availability affect nursing care and methods. However, nurses tend not to exploit professional medical databases for evidence-based medical information for their personal needs. This phenomenon has received little research attention. ObjectiveThis study aimed to address the knowledge gap around nurses' attitudes towards searching online for medical information for their personal needs (ie, for themselves and their families) by (1) evaluating the level of exposure to medical information and the effect on attitudes towards the use of online search options, (2) assessing the effect of the choice of a primary means of searching for medical information on the attitudes towards the use of online search options, and (3) gauging the influence of sociodemographic data and health status on nurses' attitudes towards searching online for medical information. MethodsNurses employed in general departments in a general hospital (34/210, 16.2%), nursing home (42/200, 21.0%), and geriatric medical center (45/180, 25.0%) in Israel were invited to complete the eHealth Impact Questionnaire (alpha=.95). Questionnaires were distributed by nurses in charge of the general hospitalization wards. The data collection period was February to March 2018. The response rate was 40.3% (121/300). ResultsNurses tended to search for medical information for personal needs on social media (24/121, 19.8%) and TV (eg, health programs, health news; 23/121, 19.0%). Nurses who chose social media as their primary means of receiving general information had a positive attitude about using the online environment as a source for medical information compared to nurses who found information through other means (t119=4.44, P<.001). Nurses exposed to medical information via social media had a positive attitude towards the use of the internet to find medical information compared to nurses who were not exposed to social media (t119=3.04, P=.003). The attitudes of nurses towards the utility of online medical information for personal needs increased with better participant health status (F2,118=3.63, P=.03). However, the attitudes of participants with a chronic disease did not differ from those of healthy participants. ConclusionsNurses in Israel are less likely to use their professional skills and knowledge to search in professional databases for evidence-based medical information for their personal needs. Instead, they prefer medical information that is easy to access and not evidence-based, such as that on social media and TV. However, these search patterns for personal use may affect their clinical role, impair quality of care, and lead to incorrect medical decisions for their patients in the health care system. Therefore, during nursing education, training for searching skills, retrieval skills, and online search techniques for evidence-based medical information is vital for evidence-based practice.